Comprehensive Analysis of Technology Integration in Nursing, Radiology, and Laboratory Services - Al Sharari , Abdullah Musaed Ali; M.Alsharari , Yousef Salman.; Alsallum , Wadha Hadi M; Alsharari , Naif Ayed B; Alanazi , Sarah Zughaydim A; Al Razq , Meshaal Mesfer A; Al Sulayyim , Abdullah Hamad M; Lasloum , Salman Saad M; Alyami , Mana Ali Saleh; Assiri, Diala Ali; Almowallad , Gabbal Abdullah M; AlQahtani , Saeed Awd Ali; et al. (Journal of Ecohumanism, 2024)
The uses of applied technology in nursing, radiology, and laboratory services are discussed in this paper with a special focus on the changes that have enhanced patients’ care, the flow, and the accuracy of diagnosis. Technological advancement in the form of EHRs, HL7s, PACS, and LIMS has changed both the operations of care ’patients’ engagement in their care. Electronic health records have brought a change in the management of patient information, increased errors, and communication gaps among healthcare givers. Omega tools that are related to the use of AI in radiology, especially in the aspect of image analysis, have enriched the accuracy as well as the speed of the interpretations. PACS has almost transformed the medical imaging area by making the ownership, reporting, and distribution of digital images more convenient. In laboratory services, the implementation of automation has greatly improved the speed at which samples can undergo some processes and improved the quality of the results from the tests compared to operations and operations, which may involve operator mistakes. Considering such advances as these technological tools, they bring about outcomes of care and care and efficient operation to remove time and cost factors in delivering services. This paper reviews previous research, investigates how these technologies are applied, and provides an analysis of outcomes that would be helpful to anyone concerned about how technology is changing these vital segments of health care for the better.